Preliminary report on the Klondike gold fields, Yukon district, Canada [electronic resource] - McConnell, R. G. (Richard George), 1857-1942.; Geological Survey of Canada. (Ottawa : Government Print. Bureau, 1900)
At head of title: Geological Survey of Canada, G.M. Dawson, C.M. G., LL. D., F.R.S., Director. Electronic reproduction. Mode of access: Internet. 44